Empowerment Of The Mosque Youth Association As A Dakwah Cadre Study On The Babussalam Mosque Youth Association Lubuk Linggau City - Maliki, Umar; Solimin, Solimin; Qomarullah, Muhammad (STAI Bumi Silampari, 2024)
The Association of Mosque Youth or popularly called IRMAS today seems to be fading its existence, amidst the dominance of the temptation of Gadgets, teenagers are no longer active in the Mosque but are busy with their respective gadgets. Applications are increasingly being made adaptive and increasingly easy to access so that the mosque becomes deserted by young people who are the successors of religion and nation. This study seeks to find out the conditions of the cadres of the Mosque Youth Association as cadres of da'wah at the Babussalam Mosque, Puncak Kemuning Village, Lubuk Linggau City. The research method used in this study is Qualitative Descriptive. Researchers conducted direct observations and interviews with the Head of the Mosque, IRMAS Mentors, IRMAS Members and the Community who witnessed the existence of IRMAS Babussalam in the midst of society. The findings of this study are that coaching for IRMAS Babussalam cadres is carried out Proactively by the Mentors and Head of the Mosque. Cadres are required to be disciplined in organizing and fostering religion at the Babussalam Mosque. The results of the study concluded that with good coaching and support, IRMAS cadres can be maximized as da'wah cadres who play a vital role in society.